Contemporary Approaches to Fault Tolerance. - Wright, Alex (Communications of the ACM, 2009)
The article discusses cost-efficient fault tolerance in web-based systems. Due to the migration of data into the realm of cloud computing, the article indicates, computer software developers are addressing systems failure at increasingly larger scales. In 2009, web-based distributed systems involve a multitude of servers, numerous stored objects, and applications which cross organization boundaries over the Internet. Commentary is provided by computer science professor Danny Dolev. Also discussed are the trade-offs involved with constructing large-scale fault-tolerant systems.